ANALISIS NILAI TAMBAH KOPI TERIPANG JAHE PRA CAMPUR SASET - Dewi, Kurnia Harlina; Nusril, Nusril; Helmiyetti, Helmiyetti; Rosalina, Yessi; Sarumpaet, Pahala (Jurnal AGRISEP, 2013)
Sea cucumbers can be used as an additive in the production of herbal coffee. It has been found in previous study that the ginger sea cucumber coffee preferred by consumers, and the composition of sea cucumber ginger coffee which is observed from chemical properties (acidity/pH and ash content) and physical properties (water content, soluble speed, and steeping levels) has also complied with SNI. Coffee industry has a promising business opportunities in an effort to increase profits or value added. This study aims to obtain an added value of ginger sea cucumber coffee packaging product. Research conducted using the Hayami method to calculate the added value. The result showed that the added value of sea cucumber ginger coffee obtained by Rp 625,858 kg, with a profit rate of 43%. The analysis shows that the sea cucumber ginger coffee can provide an added value which is highly profitable for small industries.